Late Quaternary Deglaciation, Glaciomarine Sedimentation and Glacioisostatic Recovery in the Rivière Nastapoka Area, Eastern Hudson Bay, Northern Québec - Lajeunesse, Patrick; Allard, Michel (Géographie physique et Quaternaire, 2003)
AbstractThis study presents a paleoenvironmental reconstruction of deglaciation dynamics and chronology, glaciomarine and postglacial sedimentation, as well as glacioisostatic recovery in the Rivière Nastapoka area, eastern Hudson Bay. Results indicate that the retreat of Québec-Labrador ice was mainly controlled by topography and was marked by four phases. Radiocarbon dates indicate that deglaciation began about 8.3 ka cal. BP and was characterized by a stillstand of the ice margin in the Nastapoka Hills that lead to the deposition of a drift belt in a high relative sea-level (Phase 1). After this stabilisation, the ice margin retreated rapidly eastward in a region of low relief and deposited a drape of silty clay in a falling relative sea-level (Phase 2). A second phase of stabilization of the ice margin lasted until at least 7.2 ka cal.BP on the higher shield peneplaine east of the limit of the Tyrrell Sea (Phase 3). This lead to the deposition of a belt of glaciofluvial deltas in a lower relative sea-level. Following this stillstand, the eastward retreat and subsequent ablation of the ice in central Québec-Labrador generated meltwater that transported large volumes of glacial sediments by fluvial processes and downcutting of fluvial terraces in previously deposited glaciofluvial and marine sediments (Phase 4). Glacioisostatic rebound reached 0.07 m/yr during the early phase of deglaciation and decreased to 0.04 m/yr between 6 and 5 ka cal. BP and 0.016 m/yr in the last 1000 years.